A Framework for Qualitative Analysis of Switching Techniques of Inductive Pulse Power Supply - Ayaz Ahmed; Zulkurnain Abdul-Malek; Hasmat Malik; Majed A. Alotaibi (IEEE Access)
The inductive pulse power supply (IPPS) features energy densities about an order of magnitude greater than those of a capacitive power supply, making it attractive for researchers. The literature documents various IPPS topological circuits and their derivative circuits. The literature has presented and examined several reviews on IPPS topologies; however, most of them concentrate on various Meatgrinder and XRAM-based topologies, while others lack detail and comprehensiveness. It is important for the design of the IPPS to carefully look into how to choose the primary switch, switching circuits, and topological circuits based on the pulse transformer, Meatgrinder, and XRAM. This research examines the functionality, results, and constraints of the pulse transformer, Meatgrinder, and XRAM-based IPPS circuit topologies using different switching techniques, such as stretch Meatgrinder, ICCOS, SECT, CPFU, ACC, BCSC, and TWPT. The performance of the IPPS circuits is comprehensively analyzed by examining voltage stress on the primary switch, current multiplication, and the repetition rate. Additionally, a new framework has been proposed to assist researchers in identifying switching approaches, selecting the primary switch, and determining the topology for a specific application. The purpose of this work is to serve as a valuable resource for academics and professionals interested in conducting more studies on the topic’s practical implications for IPPS.